THE ROLE OF THE OIL INDUSTRY IN ENVIRONMENTAL POLLUTION - EFFECTS AND SUGGESTED SOLUTIONS (British Journal of Global Ecology and Sustainable Development, 2023)
The issue of environmental pollution at the present time is one of the most difficult challenges facing the world, due to the high rates of pollution in its various forms, air, water and soil, and one of the most important causes of pollution is the increase. In the use of fossil fuels in general and oil in particular. Because they leave residues in the environment consisting of liquid waste, gaseous and solid materials that have a negative impact on the elements of nature and contribute to the disruption of natural structures and thus affect and reflect on life in general and on human health. and other livelihoods. It led to the death of living organisms, increased global warming, the widening of the ozone layer gap, acid rain, the spread of fires and high temperatures. Poisoning and other diseases that threaten human life, as well as heavy losses resulting from those phenomena related to pollution directly and indirectly. At every stage of the oil industry.